The spherical maximal function on the free two-step nilpotent Lie group - Fischer, Véronique (MATHEMATICA SCANDINAVICA, 2006)
We consider here the free two step nilpotent Lie group, provided with the homogeneous Korányi norm; we prove the L^p-boundedness of the maximal function corresponding to the homogeneous unit sphere, for some p.